2018
DOI: 10.3329/ijarit.v8i1.38225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of postharvest quality of edible coated mandarin at ambient storage

Abstract: An experiment was conducted to assess the influence of edible coatings on postharvest quality of mandarin during 20 days of ambient storage. Sorted fruits were washed; fruit surface water was removed and then coated with 100% liquid paraffin wax, 0.5% chitosan, 1.0% chitosan, 1.5% chitosan, and 100% coconut oil. After coating, fruit surface was air dried and kept at ambient condition (25±3 °C, 60–70% RH) and analyzed periodically for weight loss, respiration rate, firmness, decay incidence, TSS, pH, ascorbic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
3
4
0
1
Order By: Relevance
“…The fruit coating with coconut oil reduces the chances of disease growth on the fruit surface by sealing thee stomatal openings and preventing the entry of pathogens inside the fruit. Similar results are reported by Meeterenand and Aliniaeifard (2016)and Nasrin et al(2018). The spoilage loss in fruit coated with mustard and sesamum oil might be due to skin injury caused by higher concentration of oilson fruit surface.…”
Section: Discussionsupporting
confidence: 88%
“…The fruit coating with coconut oil reduces the chances of disease growth on the fruit surface by sealing thee stomatal openings and preventing the entry of pathogens inside the fruit. Similar results are reported by Meeterenand and Aliniaeifard (2016)and Nasrin et al(2018). The spoilage loss in fruit coated with mustard and sesamum oil might be due to skin injury caused by higher concentration of oilson fruit surface.…”
Section: Discussionsupporting
confidence: 88%
“…The postharvest quality parameters are influenced by the storage temperature, where the rate of deterioration increases with rise in temperature and thus contributing towards the quick senescence of fruit. Wax coating in fruit facilitates in reinforcing the natural wax on fruit and limits the transpiration losses by blocking the lenticels openings (Nasrin et al ., 2018). In the present study, the efficacy of combined application of lipid based beeswax along with the phenolic‐based SA was evaluated for the modulation of the ripening process for retention of antioxidant properties in fruit under two different storage conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Enhance shelf life, quality and also delayed the mold appearance [46] Strawberry (chitosan and carboxymethyl cellulose (CMC))…”
Section: Brsmentioning
confidence: 99%
“…Abd-El-Latif [45] reported that application of eucalyptus, thyme and lemon grass oil (at a concentration of 0.6 and 0.8%) was found effective in reducing the incidence of gray and blue molds in apple fruits. It was observed that coating of mandarin fruits with pure coconut oil (100%) enhance their shelf life, quality and also delayed the mold appearance (Nasrin et al [46]).…”
Section: Edible Coatings and Filmsmentioning
confidence: 99%